PENGARUH UMUR PINDAH TANAM DAN JENIS PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERONG (Solanum melongena L.) - Fitriany Primawati; Djarwatiningsih P.S.; Agus Sulistyono (UPN VETERAN JAWA TIMUR, 2022)
Eggplant (Solanum melongena L.) is a vegetable that is cultivated for its fruit in terms of nutrition and the price of eggplant is a commodity that is experiencing an increase in demand. This study aims to determine the age of transplanting and the best type of liquid organic fertilizer on the growth and yield of eggplant. This research was conducted in January-April 2021 in the experimental field of the Faculty of Agriculture, National Development University